Home‐Based Cardiac Rehabilitation Alone and Hybrid With Center‐Based Cardiac Rehabilitation in Heart Failure: A Systematic Review and Meta‐Analysis. Issue 16 (20th August 2019) - Imran, Hafiz M.; Baig, Muhammad; Erqou, Sebhat; Taveira, Tracey H.; Shah, Nishant R.; Morrison, Alan; Choudhary, Gaurav; Wu, Wen‐Chih
Abstract : Background: Center‐based cardiac rehabilitation (CBCR) has been shown to improve outcomes in patients with heart failure (HF). Home‐based cardiac rehabilitation (HBCR) can be an alternative to increase access for patients who cannot participate in CBCR. Hybrid cardiac rehabilitation (CR) combines short‐term CBCR with HBCR, potentially allowing both flexibility and rigor. However, recent data comparing these initiatives have not been synthesized. Methods and Results: We performed a meta‐analysis to compare functional capacity and health‐related quality of life (hr‐QOL) outcomes in HF for (1) HBCR and usual care, (2) hybrid CR and usual care, and (3) HBCR and CBCR. A systematic search in 5 standard databases for randomized controlled trials was performed through January 31, 2019. Summary estimates were pooled using fixed‐ or random‐effects (when I 2 >50%) meta‐analyses. Standardized mean differences (95% CI) were used for distinct hr‐QOL tools. We identified 31 randomized controlled trials with a total of 1791 HF participants. Among 18 studies that compared HBCR and usual care, participants in HBCR had improvement of peak oxygen uptake (2.39 mL/kg per minute; 95% CI, 0.28–4.49) and hr‐QOL (16 studies; standardized mean difference: 0.38; 95% CI, 0.19–0.57). Nine RCTs that compared hybrid CR with usual care showed that hybrid CR had greater improvements in peak oxygen uptake (9.72 mL/kg per minute; 95% CI, 5.12–14.33) but not in hr‐QOL (2 studies; standardized mean difference: 0.67; 95% CI, −0.20 to 1.54). Five studies comparing HBCR with CBCR showed similar improvements in functional capacity (0.0 mL/kg per minute; 95% CI, −1.93 to 1.92) and hr‐QOL (4 studies; standardized mean difference: 0.11; 95% CI, −0.12 to 0.34). Conclusions: HBCR and hybrid CR significantly improved functional capacity, but only HBCR improved hr‐QOL over usual care. However, both are potential alternatives for patients who are not suitable for CBCR.